National Theatre : all about theatre - McIntyre, Marina (Walker Books, 2017)
Described by Benedict Cumberbatch as "a brilliant introduction to theatre", this fascinating book by the National Theatre shows how plays like War Horse and many others are made. The book is packed with interviews with famous directors and actors, like Lenny Henry, Meera Syal, Julie Walters and Ben Whishaw, and productions like The Curious Incident of the Dog in the Night-Time and One Man, Two Guvnors. Hear from experts at the world-famous National Theatre about every aspect of stagecraft, including prop-making, set building and lighting design, and discover, from first idea to final curtain, how plays are made.